Analisis Kesulitan Membaca Permulaan pada Siswa Kelas I Berbasis Metode EGRA (Early Grade Reading Assessment) di SDN Talun 05 Kecamatan Talun Kabupaten Blitar - Nourma Oktaviarini; Nugrananda Janattaka; Nurna Listya Purnamasari (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze and describe the form of initial reading difficulties in first grade students using the Early Grade Reading Assessment (EGRA) method at SDN Talun 05, Talun District, Blitar Regency. The study uses a quantitative descriptive approach with data collection techniques through the EGRA test which covers five aspects, namely recognizing letters, reading meaningful words, reading nonsense words, reading aloud fluency and reading comprehension, and listening and comprehension. The EGRA method is used to early detect the abilities and difficulties of students' initial reading in the lower grades of elementary school. The results showed that the aspect with the highest level of difficulty was reading nonsense words with an average percentage score of 47%, followed by aspects of reading aloud fluency and reading comprehension at 50%, and aspects of listening and comprehension at 52%. Furthermore, the aspect of reading meaningful words obtained an average percentage score of 63%, while the aspect of recognizing letters became the aspect with the highest percentage at 79%. These findings indicate that students still experience difficulties in reading fluency, reading comprehension, and word pattern recognition, so the EGRA method is effectively used as an early diagnostic tool to help teachers identify students' early reading difficulties more systematically.